Epifenomenalny i istotowy wymiar muzyki w polityce - Massaka, Iwona (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2005)
The history of music has taken account of the part music has played in political processes and in particular of its epiphenomenal aspect. If any connection between music and politics is perceived at all, the role of music in politics is demonstrated to be auxiliary and accessory. Music is well known for its extreme efficiency in creating moods and, as a consequence, in creating opinions and attitudes. Therefore its role in politics is usually associated with the support for the cult of the authority in autocratic regimes and with indoctrination of all sorts. The function of music is reduced to that of providing an emotional atmosphere conducive for the transfer and reinforcement of certain ideologies in social awareness. On the other hand, it is observed that mass demonstrative opposition against imposed ideologies is also frequently expressed by means of music.
The Epiphenomenal and Individual Dimension of Music in Poland